دراسة تأثير الحركات المنعطفة إلى اليسار على أداء التقاطعات المنظمة بإشارات ضوئية - رستم أكرم; كنعان فادي; حسن حلا (Latakia University Journal -Engineering Sciences Series, 2019)
تعد الحركة المنعطفة إلى اليسار من الحركات ذات التأثير الكبير على معايير تقييم أداء التقاطعات المنظمة بإشارات ضوئية, فمن المعلوم أن مستوى الخدمة للتقاطعات ( LOS ) يؤثر بشكل ملحوظ على مستوى الخدمة للطريق ككل, كما أن مستوى الخدمة للتقاطعات يمكن أن يؤثر على السماح المتكرر لمرور العربات المنعطفة إلى اليسار, حيث أن معدلات التصادم المروري تكون أكبر في مناطق التقاطعات منها في باقي مقاطع الطريق. وبالتالي فإن ضمان انفصال العربات المنعطفة إلى اليسار بشكل آمن عن التيار المروري المتحرك بشكل مستقيم يعد شرطاً هاماً لفعالية وسلامة التقاطعات المرورية. يهدف هذا البحث إلى دراسة الحالات المختلفة لحركات الانعطاف لليسار من حيث طريقة التحكم وشكل توزع حركة الانعطاف على حارات المرور بهدف الوصول إلى تحديد طرق التحكم المروري الأكثر ملاءمة حسب حجوم المرور المنعطفة لليسار وحجوم المرور المتصادمة معها على الاتجاه المعاكس. تمت عملية التحليل والمقارنة على أربعة تقاطعات مرورية في مدينة اللاذقية وذلك مع مراعاة عدد من المتغيرات المؤثرة على حركة الانعطاف إلى اليسار. أظهرت نتائج الدراسة أن إضافة حارة خاصة للانعطاف إلى اليسار قد يخفض أزمنة تأخير حركة الانعطاف إلى اليسار ولكنه بالمقابل قد يسبب أزمنة تأخير كلية لكامل التقاطع, كما أظهرت أيضاً انخفاض في أزمنة تأخير حركة الانعطاف إلى اليسار على أغلب أذرع التقاطعات وهو ما ترافق مع زيادة في أزمنة تأخير الحركة المستقيمة على الذراع المقابل وذلك عند الانتقال من تطبيق الطور المسموح إلى تطبيق الطور المحمي. The Left-turn movements have high impact on the criteria for evaluating the performance of the Signalized intersections. It is well known that the level of service (LOS) for intersections significantly affects the level of service of the road as a whole. The level of service for intersections can have the effect to allow frequent vehicular traffic to the left-turn where the traffic collision rates are larger in areas of intersections in the rest of the road sections. Thus, to ensure the separation of vehicles to the left-turn securely current traffic moving straight is an important condition to the effectiveness and safety of traffic intersections. This research aims to study the different cases for the left-turn movements in the way the form of distributed control and turn on the movement of traffic lanes. This is so in order to identify the ways to access the most appropriate traffic control by traffic volumes of the left turn and the volumes of traffic conflicting with it on the opposite direction. The process of analysis and comparison occurs on four traffic intersections in Lattakia City taking into account a number of variables that affect the movement of turning to the left. The results showed that the addition of special turning lane to the left may reduce the delay times of the movement of turning to the left; but, in turn, it may cause the delay times of the Faculty for the entire intersection. It also shows a reduction in delay times of the left-turn movement on most of the approaches of the intersections, which coincided with an increase in delay times of through movement on opposing approach and return it when you move from application permitted phase to the protected phase.